A novel lncRNA RP11-386G11.10 reprograms lipid metabolism to promote hepatocellular carcinoma progression - Kequan Xu; Peng Xia; Xiangdong Gongye; Xiao Zhang; Shuxian Ma; Zhang Chen; Hao Zhang; Jie Liu; Yingyi Liu; Yonghua Guo; Ye Yao; Meng Gao; et al. (Elsevier, 2022)
Objective: Emerging studies suggest that long non-coding RNAs (lncRNAs) play crucial roles in hepatocellular carcinoma (HCC). A rapidly increasing number of studies have shown that metabolic changes including lipid metabolic reprogramming play a significant role in the progression of HCC. But it remains to be elucidated how lncRNAs affect tumor cell metabolism. Methods: Through analysis and screening of The Cancer Genome Atlas-Liver Hepatocellular Carcinoma (TCGA-LIHC) dataset, we found a novel lncRNA RP11-386G11.10 was overexpressed, related to prognosis, conserved and non-protein-coding in HCC and related to poor prognosis. Then, CCK-8, colony formation, Transwell invasion, wound healing assays were performed and nude mouse subcutaneous tumour formation and lung metastasis models were established to explore the effect of RP11-386G11.10 on HCC tumour growth and metastasis. Chromatography-mass spectrometry (GC-MS) and Nile red staining detected the effect of RP11-386G11.10 on lipid metabolism in HCC. Mechanistically, we clarified the RP11-386G11.10/miR-345-3p/HNRNPU signalling pathway through dual luciferase reporter, RNA immunoprecipitation (RIP) and chromatin immunoprecipitation (ChIP) assays and identified ZBTB7A as a transcription factor of RP11-386G11.10. Results: RP11-386G11.10 was overexpressed in HCC and positively correlated with tumour size, TNM stage, and poor prognosis in HCC patients. RP11-386G11.10 promoted the proliferation and metastasis of HCC cells in vitro and in vivo. Mechanistically, RP11-386G11.10 acted as a competing endogenous RNA (ceRNA) for miR-345-3p to regulate the expression of HNRNPU and its downstream lipogenic enzymes, leading to lipid accumulation in HCC cells and promoting their growth and metastasis. In addition, we identified ZBTB7A as a transcription factor of RP11-386G11.10. Moreover, HNRNPU promoted the expression of ZBTB7A in HCC cells, thereby increasing the transcriptional activity of RP11-386G11.10, and forming a positive feedback loop, ultimately leading continuous lipid accumulation, growth and metastasis in HCC cells. Conclusions: Our results indicated that the lncRNA RP11-386G11.10 was a novel oncogenic lncRNA that was strongly correlated with the poor prognosis of HCC. The ZBTB7A-RP11-386G11.10-HNRNPU positive feedback loop promoted the progression of HCC by regulating lipid anabolism. RP11-386G11.10 may become a new diagnostic and prognostic biomarker and therapy target for HCC.